Islamic Revival and National Development in the Arab World - Al-Yassini, Ayman (Journal of Asian and African studies, 1986)
Abstract The paper explores the continuing connections between religion and society in the Arab world, with a focus on Saudi Arabia, Egypt and Syria. The three countries display a continuum, ranging from total dependence (Saudi), limited reliance (Egypt), to attempted separation of religion from politics (Syria). These three Arab countries have used Islam differently, at different times, resulting in different patterns of internal co-operation and conflict. Underlying these differences, there is the context of interplay of Islamic movements and Arab governments in which, under the pressures of the modern world, the Arab governments have yet to tackle their 'legitimacy crisis' successfully. The circumstances in the three Arab countries show some of the variety of the strategies and tactics used so far, and indicate the uncertain accomplishments.